A systematic review of outcome measures used in forensic mental health research with consensus panel opinion. - Fitzpatrick, R; Chambers, J; Burns, T; Doll, H; Fazel, S; Jenkinson, C; Kaur, A; Knapp, M; Sutton, L; Yiend, J (2010)
OBJECTIVE: To describe and assess outcome measures in forensic mental health research, through a structured review and a consensus panel. DATA SOURCES: A search of eight electronic databases, including CINAHL, EMBASE and MEDLINE, was conducted for the period 1990-2006. REVIEW METHODS: In the structured review, search and medical subject heading terms focused upon two factors: the use of a forensic participant sample and the experimental designs likely to be used for outcome measurement. Data extraction included general information about the identity of the reference, specific information regarding the study and information pertaining to the outcome measures used. The consensus exercise was implemented in two stages. At the first stage, participants were asked to complete ratings about the importance of various potential areas of outcome measurement in a written consultation. At the second stage, they were asked to attend a consensus meeting to review and agree results relating to the domains, to consider and rate specific outcome instruments identified as commonly used from the structured review and to discuss strengths, weaknesses and future priorities for outcome measurement in forensic mental health research. RESULTS: The final sample of eligible studies for inclusion in the review consisted of 308 separate studies obtained from 302 references. The consensus group agreed on 11 domains of forensic mental health outcome measurement, all of which were considered important. Nine different outcome measure instruments were used in more than four different studies. The most frequently used outcome measure was used in 15 studies. According to the consensus group, many domains beyond recidivism and mental health were important but under-represented in the review of outcomes. Current instruments that may show future promise in outcome measurement included risk assessment tools. The outcome measure of repeat offending behaviour was by far the most frequently used, occurring in 72% of the studies included in the review. Its measurement varied with position in the criminal justice system, offence specification and method of measurement. The consensus group believed that recidivism is only an indication of the amount of antisocial acts that are committed. CONCLUSIONS: A wide range of domains are relevant to assessing outcomes of interventions in forensic mental health services. Evaluations need to take account of public safety, but also clinical, rehabilitation and humanitarian outcomes. Recidivism is a very high priority; the public expects interventions that will reduce future criminal behaviour. Greater attention needs to be given to validity of measurement, given the enormous variety of approaches to measurement. More research is needed on methods to take account of the heterogeneity of seriousness of forms of recidivism in outcome measurement. Validity of self-report instruments regarding recidivism also needs examination by further research. Mental health is clearly also an important dimension of outcome. The review provides clear support for the view that domains such as quality of life, social function and psychosocial adjustment have not been extensively employed in forensic mental health research, but are relevant and important issues. The role of such instruments needs more consideration.